IMPLEMENTASI PRINSIP DAN PROSEDUR PENGELOLAAN KEUANGAN SEKOLAH DI SMA MUHAMMADIYAH 1 PALEMBANG - Fatra, Fatra; Harapan, Edi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
The objectives of this research were 1) describing the funding of educational resources in High School Muhammadiyah 1 Palembang; 2) describing the realization and allocation the funding in High School Muhammadiyah 1 Palembang; and 3) describing the characteristics of accountability the funding in High School Muhammadiyah 1 Palembang. This research was qualitative. We studied the problems not to prove neither to reject the hypothesis that was made in the past nor to process data and analyze problem in non-numerically. Sources of income in High School Muhammadiyah 1 Palembang listed on Budget Plan (RAPBS). The sources were come from APBN, APBD of Province, and APBD of Palembang. The allocation of funds generally used to make equalization in education and conducted to improve the quality of education. Financial accountability was created by treasurer and principal and it was known by the school committee monthly, including the supporting data, proves of expense and details of expense. Â Keyword: Finance, Principle and Procedure of Management, High School Muhammadiyah 1 Palembang.